Biopolitics and Displaced Bodies - Ince, Güler (Göttingen, 2018)
For a geographic “place” to become a “homeland” or “home”, a community sharing a common cul- tural background has to take root there. The acquired place then forms part of the “body” of that community. Displacement turns individuals and communities into fragile entities by cutting their connection with their “place” and depriving them of their histories and bodies. The concepts of “borders” and “biopolitics” have gained prominence in the context of liberal nation states. In the view of persistent banishment, forced displacement, and population exchange in many parts of the world, contemporary border enforcement based on biopolitics serves to maintain control over bod- ies. This article will analyse depictions of the phenomena of exile, migration, immigration, and ref- uge/asylum in modern art with reference to the concept of biopolitics. Damit ein geographischer „Ort“ zur „Heimat“ oder zum „Zuhause“ wird, muss eine Gemeinschaft, die einen gemeinsamen kulturellen Hintergrund hat dort Wurzeln schlagen. Der erworbene Ort bildet dann einen Teil des „Körpers“ dieser Gemeinschaft. Verdrängung verwandelt Individuen und Ge- meinschaften durch das Abschneiden von der eigenen Geschichte und ihres Gemeinschaftskörpers in fragile Gebilde. Die Begriffe „Grenzen“ und „Biopolitik“ haben im Kontext liberaler Nationalstaaten an Bedeutung gewonnen. Angesichts von andauernder Verbannung, Zwangsvertreibung und Bevöl- kerungsaustausch in vielen Teilen der Welt, dient die moderne Grenzkontrolle auf der Basis von Bio- politik der Aufrechterhaltung der Überwachung von Körpern. In diesem Artikel werden die Phäno- mene des Exils, der Migration, der Immigration und des Asyls in der modernen Kunst anhand des Konzepts der Biopolitik analysiert.
Challenging Message and Representation in Refugee Art
Keywords: Körper; Migration; Kunst; Repräsentation; Biopolitik; 700 Künste, Bildende und angewandte Kunst; Vertreibung; Exil; Körper; Biopolitik; Repräsentation; visuelle Kunst